The economic benefits of potable water supply projects to households in developing countries - Whittington, Dale (Asian Development Bank, 1994)
In this report the authors argue that there is a need for both improved procedures and better practice in the estimation of the economic benefits of water supply sector, and then present several appoaches that can be used to estimate the economic benefits to households of potable water supply